2009
DOI: 10.1038/onc.2009.363
|View full text |Cite
|
Sign up to set email alerts
|

Differential phosphorylation of the docking protein Gab1 by c-Src and the hepatocyte growth factor receptor regulates different aspects of cell functions

Abstract: The docking protein Grb2-associated binder1 (Gab1) has a central role in the integration of the growth-factor signaling. In this study, we aimed to examine the significance of Src-mediated Gab1 phosphorylation in the hepatocyte growth factor (HGF) signaling. Using both mutagenesis and mass spectrometry approaches, Y242, Y259, Y317, Y373 and Y627 of Gab1 were identified to be phosphorylated by c-Src. It is interesting to note that the binding of the tyrosine phosphatase SHP2 to the Y627 antagonized the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…In particular, we have previously shown that flow activates the PI3K/Akt/eNOS pathway via Src kinase-dependent transactivation of VEGFR2 [6]. It has also been demonstrated that Gab1 Y627 is phosphorylated by Src in vitro [30]. Hereby, we investigated the role of Src kinase in flow- and HGF-induced Gab1 tyrosine phosphorylation.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…In particular, we have previously shown that flow activates the PI3K/Akt/eNOS pathway via Src kinase-dependent transactivation of VEGFR2 [6]. It has also been demonstrated that Gab1 Y627 is phosphorylated by Src in vitro [30]. Hereby, we investigated the role of Src kinase in flow- and HGF-induced Gab1 tyrosine phosphorylation.…”
Section: Resultsmentioning
confidence: 95%
“…It has been reported that Src kinase is involved in flow [6, 19, 29] and HGF [18, 30, 31] signaling in ECs. In particular, we have previously shown that flow activates the PI3K/Akt/eNOS pathway via Src kinase-dependent transactivation of VEGFR2 [6].…”
Section: Resultsmentioning
confidence: 99%
“…The phosphorylation of Tyr-187 on MARK1 (downstream of EGFR/Her2 signaling pathway) is required for its activation 34 . The phosphorylation of Tyr-627 of GAB1 confers binding and activation of the tyrosine phosphatase SHP2 35 . Tyr-453 in GAREM is critical for binding of SHP2 to GAREM in MARK1 activation upon EGF stimulation 36 .…”
Section: Resultsmentioning
confidence: 99%
“…Gab proteins are tyrosine phosphorylated following activation of diverse receptor types, including specific RTKs, B‐ and T‐cell antigen receptors and β1‐integrin, and depending on the cellular context, this may be mediated by the RTK itself, and/or kinases of the Src, Syk/ZAP‐70 or JAK families [7]. Interestingly, a recent study reported that c‐Src and c‐Met exhibit contrasting selectivity towards particular Gab1 phosphorylation sites, and that phosphorylation of four tyrosine residues by c‐Src contributes to hepatocyte growth factor‐induced DNA synthesis [12]. Gab/DOS tyrosine phosphorylation leads to binding of specific SH2 domain‐containing effectors, the best‐characterized of which is the SH2 domain‐containing protein tyrosine phosphatase Shp2.…”
Section: The Gab/dos Familymentioning
confidence: 99%